On the need of objective vigilance monitoring: Effects of sleep loss on target detection and task-negative activity using combined EEG/fMRI - Czisch, Michael; Wehrle, Renate; Harsay, Helga A.; Wetter, Thomas C.; Holsboer, Florian; Sämann, Philipp G.; Drummond, Sean P. (Frontiers in Neurology, 2012)
Sleep loss affects attention by reducing levels of arousal and alertness. The neural mechanisms underlying the compensatory efforts of the brain to maintain attention and performance after sleep deprivation (SD) are not fully understood. Previous neuroimaging studies of SD have not been able to separate the effects of reduced arousal from the effects of SD on cerebral responses to cognitive challenges. Here, we used a simultaneous electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) approach to study the effects of 36 h of total sleep deprivation (TSD). Specifically, we focused on changes in selective attention processes as induced by an active acoustic oddball task, with the ability to isolate runs with objective EEG signs of high (SDalert) or reduced (SDsleepy) vigilance. In the SDalert condition, oddball task-related activity appears to be sustained by compensatory co-activation of insular regions, but task-negative activity in the right posterior node of the default mode network is altered following TSD. In the SDsleepy condition, oddball task-positive activity was massively impaired, but task-negative activation was showing levels comparable with the control condition after a well-rested night. Our results suggest that loss of strict negative correlation between oddball task-positive and task-negative activation reflects the effects of TSD, while the actual state of vigilance during task performance can affects either task-related or task-negative activity, depending on the exact vigilance level.